2019
DOI: 10.1016/j.trci.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

New insight into Alzheimer's disease: Light reverses Aβ‐obstructed interstitial fluid flow and ameliorates memory decline in APP/PS1 mice

Abstract: Introduction Pharmacological therapies to treat Alzheimer's disease (AD) targeting “Aβ” have failed for over 100 years. Low levels of laser light can disassemble Aβ. In this study, we investigated the mechanisms that Aβ‐blocked extracellular space (ECS) induces memory disorders in APP/PS1 transgenic mice and addressed whether red light (RL) at 630 nm rescues cognitive decline by reducing Aβ‐disturbed flow of interstitial fluid (ISF). Methods We compared the heating effects on the brains of rats illuminated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 48 publications
(68 reference statements)
0
32
0
Order By: Relevance
“…Changes in the ISS have also been reported in other diseases, such as Parkinson's disease [116], multiple sclerosis [117,118], and epilepsy [17,119]. Moreover, another study in a mouse model of AD by Yue and associates suggested that the destruction of beta-amyloid deposits in the ECS using a light-emitting diode with red light facilitated not only the recovery of ISF drainage but also rescued cognitive function [15]. This study suggested a new avenue for treating AD by targeting beta-amyloid in the ISS.…”
Section: Status Of Iss In Neurological Disordersmentioning
confidence: 73%
See 1 more Smart Citation
“…Changes in the ISS have also been reported in other diseases, such as Parkinson's disease [116], multiple sclerosis [117,118], and epilepsy [17,119]. Moreover, another study in a mouse model of AD by Yue and associates suggested that the destruction of beta-amyloid deposits in the ECS using a light-emitting diode with red light facilitated not only the recovery of ISF drainage but also rescued cognitive function [15]. This study suggested a new avenue for treating AD by targeting beta-amyloid in the ISS.…”
Section: Status Of Iss In Neurological Disordersmentioning
confidence: 73%
“…Significant transformations ensue in ISS during the development of the brain due to events such as neurogenesis, neuronal migration and differentiation, expansion of dendritic tree, synaptogenesis, gliogenesis, synaptic stripping by microglia, and myelination [1,[5][6][7][8][9][10]. The geometry of the brain ISS also undergoes modification in aging due to the loss of synapses, neurons, dendritic regression, changes in morphology and numbers of glia, senoinflammation, and deposition of amyloid plaques [11][12][13][14][15]. In conditions such as epilepsy, the synchronized firing of a population of neurons may considerably change the geometry of ISS as well as the ISF drainage [16].…”
Section: The Geometry Of the Brain Issmentioning
confidence: 99%
“…Yue et al [33] used APP/PS1 AD model mice treated, APP/PS1 control mice and healthy C57BL/6 mice as a negative control. The treatment was with photobiomodulation by LED 630 nm with application of 40 minutes and light intensity of 0.55 mW/cm2 in the skull and abdomen 5 days a week for 2 months.…”
Section: Transcranial Photobiomodulation (Using Led)mentioning
confidence: 99%
“…More recently, MRI was applied to show that the presence of β-amyloid in the APP/PS1 Alzheimer's disease mouse model was associated with reduced perivascular ISF flow and glymphatic system function. Notably, this effect could be effectively reversed through controlled heating of the brain tissue by transcranial illumination with red light over a period of 2 months, and this was further associated with rescue of impaired spatial learning (Yue et al, 2019).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%